A Bistable Variable Infrared Emissivity Device Based on Reversible Silver Electrodeposition. (1st June 2022) - Tao, Xin; Liu, Dongqing; Liu, Tianwen; Meng, Zhen; Yu, Jinshan; Cheng, Haifeng
Abstract: Reversible silver electrodeposition (RSE) can dynamically modulate visible light and infrared radiation through the reversible electrodeposition and dissolution of silver layer. However, the RSE device with bistability better than 2 h has not been reported, because the deposited silver layer may dissolve automatically without driving voltage. Here, a variable infrared emissivity device based on RSE with 24 h excellent bistability is demonstrated. A silver layer fixed at the counter electrode is used as the charge mediator, which reforms the electrochemical reactions of the counter electrode and is the key for obtaining bistability. Effects of electrolyte composition and driving voltage on the bistability are studied, and the driving voltage affects the bistability of RSE devices. This RSE device can be enlarged to 5 × 5 cm 2 with uniform emissivity change of 0.48 in 2.5–25 µm using silicon wafer as the infrared transparent working electrode substrate, and display discontinuous thermal patterns through incorporating a dielectric pattern layer. The cyclability and device failure mechanism is analyzed. With the excellent bistability, the proposed RSE devices provide great application prospects in the fields of dynamic infrared information display, adaptive infrared camouflage, and smart thermal management. Abstract : In this research, a silver layer fixed at the counter electrode is used as the charge mediator to enhance the open‐circuit stability of reversible silver electrodeposition devices. The driving voltage effect on the bistability of reversible silver electrodeposition is studied. Devices with 24 h excellent bistability are constructed. Enlarged and patterned devices are also fabricated based on this device structure.